KEPENTINGAN BRAZIL MENJADI TUAN RUMAH PIALA DUNIA FIFA 2014 - Seri Afenita Pinem (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research describes about the interests of Brazil in 2014 FIFA World Cup event. World Cup is one of the sporting events that is highly anticipated by many people because football itself is a very popular sport. 2014 FIFA World Cup hosted by Brazil raised many pros and cons about the ability of Brazil to host the mega sport event. Many brazilians even protest against the world cup because they think that is just waste of money.The research was conducted using library research methods where the data and information obtained from sources which are relevant to the problem of this research. The study would be analyzed with mercantilism perspective, rational choice theory by Stephen M. Walt and the concept of national interest by Donald E. Nuechterlein.The result of the research shows that Brazil have national interest to achieve by hosting 2014 FIFA world cup. Economically, the government of Brazil hopes Brasil will get great income from tourist visits during the world cup and make Brasil become a tourist destination country. Politically, the government want to increase the prestige of the country by organizing the event successfully. This chance is also used by President of Brazil, Dilma Rousseff to win the presidential election in Brazil.Keywords : National Interest, World Cup, FIFA